2017
DOI: 10.2166/wh.2017.283
|View full text |Cite
|
Sign up to set email alerts
|

The risk of cancer as a result of elevated levels of nitrate in drinking water and vegetables in Central India

Abstract: The objective of the present study was to determine the effect of nitrates on the incidence of gastrointestinal (GI) cancer development. Nitrate converted to nitrite under reducing conditions of gut results in the formation of N-nitrosamines which are linked to an increased gastric cancer risk. A population of 234 individuals with 78 cases of GI cancer and 156 controls residing at urban and rural settings in Nagpur and Bhandara districts of India were studied for 2 years using a case-control study. A detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…In elevated concentrations, they can cause a disease called child methaemoglobin, lethal for children, once when in the bloodstream, nitrates are reduced to nitrite, competing with iron for the free oxygen, turning the blood blue (WHO ). In the body, nitrates can also react with amines and amides by nitrosation to form N‐nitrous compounds, which are proven carcinogens (Taneja et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In elevated concentrations, they can cause a disease called child methaemoglobin, lethal for children, once when in the bloodstream, nitrates are reduced to nitrite, competing with iron for the free oxygen, turning the blood blue (WHO ). In the body, nitrates can also react with amines and amides by nitrosation to form N‐nitrous compounds, which are proven carcinogens (Taneja et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrate is the last oxidation phase of organic matter, and therefore, its presence in water is attributed to contamination from agricultural, industrial, and/or urban activities, especially related to animal manure, nitrogen fertilizers, Research Article domestic and industrial sewage, and dumps residues (Taneja, Labhasetwar, Nagarnaik, & Ensink, 2017). In Batman, Turkey, high concentrations of nitrate were reported in groundwater samples collected from areas where agriculture and livestock activities are common (Nalbantcilar & Pinarkara, 2016).…”
Section: Research Articlementioning
confidence: 99%
“…Nitrate concentrations in groundwater were reported for Morocco, Niger, Nigeria, Senegal, India-Pakistan, Japan, Lebanon, Philippines and Turkey with maximum levels in Senegal (median 42.9 mg/L NO 3 -N) [ 5 ]. In India, nitrate in drinking water supplies is particularly high in rural areas, where average levels have been reported to be 45.7 mg/L NO 3 [ 27 , 28 ] and 66.6 mg/L NO 3 [ 28 ]; maximum levels in drinking water exceeded 100 mg/L NO 3 in several regions [ 27 , 29 ]. Extremely high levels of nitrate have been reported in The Gaza Strip, where nitrate reached concentrations of 500 mg/L NO 3 in some areas, and more than 50% of public-supply wells had nitrate concentrations above 45 mg/L NO 3 [ 30 ].…”
Section: Drinking Water Nitrate Exposures In the United States Andmentioning
confidence: 99%
“…The remaining 62 studies underwent full-text evaluations; 38 of these were excluded for not assigning nitrite or nitrate as exposure markers (n=21), for reporting the sample population (n=12), or for being a systematic review (n=5). Ultimately, 18 case-control studies and 6 cohort studies were included in the final quantitative meta-analysis [2245]. No additional eligible studies were found in the manual search of the references of retrieved studies.…”
Section: Resultsmentioning
confidence: 99%